2017
DOI: 10.1042/bsr20170021
|View full text |Cite|
|
Sign up to set email alerts
|

Role of ESAT-6 in renal injury by regulating microRNA-155 expression via TLR4/MyD88 signaling pathway in mice with Mycobacterium tuberculosis infection

Abstract: The study aims to investigate the underlying mechanism involved in the early secretory antigenic target-6 (ESAT-6) in renal injury through regulation of the expression of miR-155 through the oll-like receptor (TLR)-4 (TLR4)/myeloid differentiation factor 88 (MyD88) signaling pathway in Mycobacterium tuberculosis (MTB)-infected mice. Sixty C57BL/6 mice with MTB-induced renal injury were randomly assigned into control, MTB, mimic, inhibitor, inhibitor + ESAT6, and inhibitor + ESAT6 + TAK242 groups. Body weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Also, miR-155 increased mRNA expression of TLR4, MyD88, TNF-␣, IL-17, and IFN-␥ through the TLR4 signaling pathway, promoting the progression of infection, leading to renal injuries in extra PTB disease in mice (Fig. 3I) (104).…”
Section: Role Of Validated Mirna In Different Stages Of Diseasementioning
confidence: 99%
“…Also, miR-155 increased mRNA expression of TLR4, MyD88, TNF-␣, IL-17, and IFN-␥ through the TLR4 signaling pathway, promoting the progression of infection, leading to renal injuries in extra PTB disease in mice (Fig. 3I) (104).…”
Section: Role Of Validated Mirna In Different Stages Of Diseasementioning
confidence: 99%
“…Studies assessing Mtb proteins and kidney injury found the Mtb antigen, ESAT-6, contributed to renal injury in mice injected with a high dose of ESAT-6 by upregulating the expression of pro-inflammatory microRNA-155 via the MyD88 innate cell pathway (275,277,278). While the dose of ESAT-6 used in these studies may not reflect those found in physiological disease, this evidence may show a cyclical worsening of disease in CKD/TB coinfection exacerbated by kidney inflammation caused by TB and CKD independently.…”
Section: Antibodies and Immunity In Chronic Kidney Disease And Tubercmentioning
confidence: 99%
“…Murine BMDCs can produce TNF-α and IL-1β in response to ESAT6 (21). In addition, TLR4 is essential for ESAT6-induced IFN-β expression in macrophages (22), and TLR4 expression is upregulated in the renal tissues of mice with M. tuberculosis - or ESAT6-induced renal injury (25). It was also reported that TLR2 is important for ESAT6-mediated immune regulation (18).…”
Section: Resultsmentioning
confidence: 99%